2012
DOI: 10.1002/pd.3934
|View full text |Cite
|
Sign up to set email alerts
|

First trimester risk assessment for trisomy 21 in twin pregnancies combining nuchal translucency and first trimester biochemical markers

Abstract: The combined test in twins appears to be a good method for Down syndrome screening with a high detection rate and an acceptable false-positive rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
1
22
0
4
Order By: Relevance
“…When differentiating by chorionicity, this series showed that the combined first-trimester test allowed for detection of all the cases of Down syndrome in the 554 fetuses evaluated, with an FPR of 6.4% in dichorionic twins and 3.8% in monochorionic twins. Similar results were obtained by Prats et al, 35 who showed reductions in the FPR to 5.7% in dichorionic and 4.4% in monochorionic twins, especially in those with advanced maternal age. The improved performance characteristics in monochorionic twins is expected, as both fetuses are affected and the abnormal analyte values trend in the same direction, whereas in dichorionic twins there may be discordance.…”
Section: Ntsupporting
confidence: 88%
See 4 more Smart Citations
“…When differentiating by chorionicity, this series showed that the combined first-trimester test allowed for detection of all the cases of Down syndrome in the 554 fetuses evaluated, with an FPR of 6.4% in dichorionic twins and 3.8% in monochorionic twins. Similar results were obtained by Prats et al, 35 who showed reductions in the FPR to 5.7% in dichorionic and 4.4% in monochorionic twins, especially in those with advanced maternal age. The improved performance characteristics in monochorionic twins is expected, as both fetuses are affected and the abnormal analyte values trend in the same direction, whereas in dichorionic twins there may be discordance.…”
Section: Ntsupporting
confidence: 88%
“…In addition, some centers adjust for chorionicity, as PAPP-A and free B-hCG levels are lower in monochorionic twins than dichorionic twins. 35,41,42 However, in chromosomally discordant twins, usually dichorionic, an unaffected twin can mask the presence of an affected twin with this calculation, making the tests less sensitive. Therefore, using a combination of NT measurements and first-trimester biomarkers appears to be more accurate in diagnosing aneuploidy rates in twins than using biochemical markers alone, reaching detection rates of 75% to 90%.…”
Section: Ntmentioning
confidence: 97%
See 3 more Smart Citations